2011
DOI: 10.1002/rmv.707
|View full text |Cite
|
Sign up to set email alerts
|

Codon usage roles in human papillomavirus

Abstract: Human papillomavirus (HPV) genomes, similar to other virus genomes, frequently have a G + C content significantly different from their host species. The HPV genomes show a strong codon usage bias to 18 codons, with 14 showing T at the third position amongst degenerately encoded amino acids. The codon usage pattern in HPV genome plays an important role, which regulates low or non-translational expression of the viral capsid genes and results in very weak protein expression of oncogenes in a wide range of mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 111 publications
0
30
0
Order By: Relevance
“…The particular codon usage (codon bias) of an organism reflects the evolutionary forces acting within its genome (37,38) and contributes to drastically reducing the actual sequence space. In the virus world, at least four mechanisms underlying such a bias exist: mutational bias or the specific nucleotide composition (39-42); translation selection, or the optimal codon adaptation to the tRNA pool in order to get a highly efficient and accurate translation (43)(44)(45)(46)(47); fine-tuning translation kinetics selection, or the right combination of abundant and rare codons to allow a regulated ribosome traffic rate that temporally separates protein folding events, ensuring "beneficial" and avoiding "unwanted" interactions within the growing peptide (17); and selection for mechanisms to escape the antiviral cell responses (48,49). Except the last, all these mechanisms are shared in all organisms (50), and it is likely that a combination of all of them is the actual evolutionary force shaping the codon usage of HAV.…”
Section: Discussionmentioning
confidence: 99%
“…The particular codon usage (codon bias) of an organism reflects the evolutionary forces acting within its genome (37,38) and contributes to drastically reducing the actual sequence space. In the virus world, at least four mechanisms underlying such a bias exist: mutational bias or the specific nucleotide composition (39-42); translation selection, or the optimal codon adaptation to the tRNA pool in order to get a highly efficient and accurate translation (43)(44)(45)(46)(47); fine-tuning translation kinetics selection, or the right combination of abundant and rare codons to allow a regulated ribosome traffic rate that temporally separates protein folding events, ensuring "beneficial" and avoiding "unwanted" interactions within the growing peptide (17); and selection for mechanisms to escape the antiviral cell responses (48,49). Except the last, all these mechanisms are shared in all organisms (50), and it is likely that a combination of all of them is the actual evolutionary force shaping the codon usage of HAV.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression of HPV in squamous epithelial cells is linked to the differentiation and function of the epithelial cells (Zheng and Baker, 2006;Zhao and Chen, 2011). The complete nucleotide sequence of the HPV genome was determined in 1985 (Seedorf et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several studies on the HPV genome (Zhou et al, 1999;Zhao et al, 2003;Zhao and Chen, 2011), there is dearth of information on synonymous codon usage of HPV and factors that influence it. To obtain better and integrated understanding of synonymous codon usage of HPV, codon usage patterns of 39 HPV genomes were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…It is the most common cancer in female genital system. Moreover, it is an important malignancy in the world [2]. It has been found that more than 99% of cervical cancers are induced by human papilloma virus (HPV) [3].…”
Section: Introductionmentioning
confidence: 99%